Capacitação de profissionais para o uso do protocolo nichd em entrevistas investigativas de abuso sexual infantil - Blefari, Carlos Aznar (2014)
The goal of this study was to train professionals in the use of the NICHD investigativeinterview protocol. The NICHD (National Institute of Child Health and HumanDevelopment) investigative interview protocol was developed based on best practices ininvestigative interview and aspects of child development. This is the tool with morestudies validating their effectiveness in the field (Lamb, Hershkowitz, Orbach & Esplin,2008). The protocol provides a high amount of open-ended questions thus decrease theindex of suggestibility increasing the amount of detail provided by the children.Participate in the study two psychologists (67 %) and a social work (33 %). A trainingprogram was developed with four interventions versions based on the studies of Lamb,Sternberg, Orbach, Hershkowitz, Esplin and Horowitz (2002); Cyr and Lamb (2009)and Stewart, Katz and La Rooy (2011) . The design of the study was A-B-C-D-E. Thebehavior of each participant was assessed by investigative interviews realized betweeneach intervention program, beginning with an assessment of operant level. A contentanalysis of aspects related to conducting the interview as well as dynamic,consequences and disclosure of sexual abuse was made. The results show animprovement in the quality of the interviews. The participants began to use more openendedquestions and lower closed questions in their professional practices. Weemphasize the importance of conducting a training program that includes theoretical,practical aspects and ongoing supervisions with individual feedback in each interview